2022
DOI: 10.3390/foods11182798
|View full text |Cite
|
Sign up to set email alerts
|

Food Bloggers on the Twitter Social Network: Yummy, Healthy, Homemade, and Vegan Food

Abstract: Many people now consider social networking to be an indispensable tool. There are now over 4.6 billion social media users, who leave a digital footprint through their online interactions. These big data provide enormous research potential for identifying the social and cultural aspects of the monitored topic. Moreover, the use of social media platforms has been found to have an impact on eating habits. The analysis of these social networks is thus essential to understand the factors that influence eating habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 83 publications
0
5
0
1
Order By: Relevance
“…El segundo investiga cómo las discusiones en redes sociales pueden apoyar el cambio social en la alimentación hacia la sostenibilidad, analizando para ello la actividad en Facebook vinculada al Finnish Vegan Challenge (Laakso, Niva, Eranti y Aapio, 2022). En 2022 se encuentra un artículo que habla sobre la representación de los hombres y la masculinidad en una comunidad vegana online de Reddit (Brookes y Chalupnik, 2022a); otro que analiza el contenido de blogueros que hablan sobre comida en Twitter (Pilar et al, 2022); y otro que analiza la comunicación de las influencers veganas españolas en Instagram (Romero-Cantero, González-Díaz y Quintas-Foufe, 2022).…”
Section: Veganismo/vegetarianismo Y Redes Socialesunclassified
“…El segundo investiga cómo las discusiones en redes sociales pueden apoyar el cambio social en la alimentación hacia la sostenibilidad, analizando para ello la actividad en Facebook vinculada al Finnish Vegan Challenge (Laakso, Niva, Eranti y Aapio, 2022). En 2022 se encuentra un artículo que habla sobre la representación de los hombres y la masculinidad en una comunidad vegana online de Reddit (Brookes y Chalupnik, 2022a); otro que analiza el contenido de blogueros que hablan sobre comida en Twitter (Pilar et al, 2022); y otro que analiza la comunicación de las influencers veganas españolas en Instagram (Romero-Cantero, González-Díaz y Quintas-Foufe, 2022).…”
Section: Veganismo/vegetarianismo Y Redes Socialesunclassified
“…In the vein of the restaurant influencers' importance, the marketers give them a related name, the food bloggers (Cuomo et al, 2017). Food bloggers are influencers who represent their opinions and evaluations for customers about food value, taste, prices, and recommendations (Pilař et al, 2022). According to Mainolfi et al (2021), food bloggers are the dominant potential consumers' intentions about specific types of foods.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Commercial tomato pastes were manufactured in industrialised environments in contrast with homemade households; commercial tomato paste had a better quality in terms of the total phenolic content, total flavonoid content, and antioxidant values (Katırcı et al, 2020). Pilař et al (2022) discovered that food bloggers most frequently used the hashtags #yummy, #healthy, # homemade, and #vegan in trade via the internet and social media marketing. Griffith et al (2022) found that the selling price of homemade meals has increased compared to the cost of ready-to-eat food.…”
Section: Marketing Challenges In Selling Homemade Foodmentioning
confidence: 99%